METHODS TAXONOMIC EVALUATION OF THE IMPACT OF FINANCIAL SECURITY ELEMENTS ON PARAMETERS CAPABILITIES OF SERVICE AND PERFORMANCE OF COMBAT MISSIONS CONNECTIONS NATIONAL GUARD OF UKRAINE - Gorodnov, V. P.; Pavlenko, S. О.; Ovcharenko, V. V. (Honor and Law, 2019)
The technique, which allows you to perform taxonomic assessment of the impact of the financial elements of the software on the possibility of the service and combat missions formations, military units of the National Guard of Ukraine.